CT mimics of peritoneal carcinomatosis - Smiti, S (Medknow Publications, 2010)
Peritoneal carcinomatosis is a term used to describe widespread metastases of cancerous tumors in the peritoneal cavity. It is most common in carcinomas of the gastrointestinal tract (GIT) and ovaries, and must be considered to be the main diagnosis even when the primary is not known. A wide variety of disease processes mimic peritoneal carcinomatosis. Precise diagnosis based on imaging alone is often difficult and very often the final diagnosis is only obtained after appropriate histopathology or microbiology.